2016
DOI: 10.1108/mhrj-12-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Non-attendance at psychological therapy appointments

Abstract: Purpose Research demonstrates that non-attendance at healthcare appointments is a waste of scarce resources; leading to reduced productivity, increased costs, disadvantaged patients through increased waiting times and demoralised staff. The purpose of this paper is to investigate non-attendance and implemented interventions to improve practice. Design/methodology/approach A mixed methods service audit took place in a primary care psychological therapies service. Existing service guidelines and reporting syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 45 publications
6
41
1
3
Order By: Relevance
“…Our overall level of non-attendance at a psychiatry appointment (18.6 %) was at a level that is similar to other studies of referral to mental health services [17], a study in the US of attendance of 123 patients with dissociative seizures referred in the US (20 %) [26] and a previous study of patients with functional neurological disorders referred by neurologists to psychiatrists [19], but higher than levels of non-attendance to general medical services (which tend to run at 5-10 %). This data was obtained in the course of recruiting patients to an RCT reducing the generalisability to general neurological practice.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our overall level of non-attendance at a psychiatry appointment (18.6 %) was at a level that is similar to other studies of referral to mental health services [17], a study in the US of attendance of 123 patients with dissociative seizures referred in the US (20 %) [26] and a previous study of patients with functional neurological disorders referred by neurologists to psychiatrists [19], but higher than levels of non-attendance to general medical services (which tend to run at 5-10 %). This data was obtained in the course of recruiting patients to an RCT reducing the generalisability to general neurological practice.…”
Section: Discussionsupporting
confidence: 88%
“…Reasons often given by patients for non-attendance include forgetting, apathy, illness, work commitments and clerical errors [17]. Psychiatric appointments have a higher rate of missed appointments than general medical ones (20 % vs 10 % in one study [17]). Specific reasons related to psychiatric settings include being unhappy with the referral in the first place (5/29 psychiatric new patients in one study [18]), stigma and fear of what might happen during the appointment.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies showed that patients who attended a greater number of treatment sessions showed a better clinical recovery (Gyani et al, 2011). However, there are a high proportion of individuals failing to complete the full course of their offered treatment (Chan and Adams, 2014) and focusing on the drop-out rate of treatment is considered to be an important area of research (Binnie and Boden, 2016). Yet little is known about the experiences of patients who discontinue their therapy, if they feel better or worse and what may contribute to their recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that different components could predict the drop-out rates from treatment including a low standard of education (Keijsers et al, 2001), higher levels of social deprivation (Grant et al, 2012;Self et al, 2005), psychological distress (Saxon et al, 2017), avoidance (Lincoln et al, 2005), high depression (Jarrett et al, 2013), low motivation (Keijsers et al, 2001), higher level of risk to self (Binnie and Boden, 2016), type of therapy format patients received (Karekla et al, 2019) and personal circumstances such as work commitments and physical illness. Rachael et al (2010) reported that drop-out rate for psychoeducation courses was more significantly associated with personal circumstances (75%) than dissatisfaction with the course (25%).…”
Section: Introductionmentioning
confidence: 99%